Interaction analysis between HLA-DRB1 shared epitope alleles and MHC class II transactivator CIITA gene with regard to risk of rheumatoid arthritis. - Marcus Ronninger; Maria Seddighzadeh; Morten Christoph Eike; Darren Plant; Nina A Daha; Beate Skinningsrud; Jane Worthington; Tore K Kvien; Rene E M Toes; Benedicte A Lie; Lars Alfredsson; Leonid Padyukov (PLoS ONE, 2012)
HLA-DRB1 shared epitope (SE) alleles are the strongest genetic determinants for autoantibody positive rheumatoid arthritis (RA). One of the key regulators in expression of HLA class II receptors is MHC class II transactivator (CIITA). A variant of the CIITA gene has been found to associate with inflammatory diseases.We wanted to explore whether the risk variant rs3087456 in the CIITA gene interacts with the HLA-DRB1 SE alleles regarding the risk of developing RA. We tested this hypothesis in a case-control study with 11767 individuals from four European Caucasian populations (6649 RA cases and 5118 controls).We found no significant additive interaction for risk alleles among Swedish Caucasians with RA (n = 3869, attributable proportion due to interaction (AP) = 0.2, 95%CI: -0.2-0.5) or when stratifying for anti-citrullinated protein antibodies (ACPA) presence (ACPA positive disease: n = 2945, AP = 0.3, 95%CI: -0.05-0.6, ACPA negative: n = 2268, AP = -0.2, 95%CI: -1.0-0.6). We further found no significant interaction between the main subgroups of SE alleles (DRB1*01, DRB1*04 or DRB1*10) and CIITA. Similar analysis of three independent RA cohorts from British, Dutch and Norwegian populations also indicated an absence of significant interaction between genetic variants in CIITA and SE alleles with regard to RA risk.Our data suggest that risk from the CIITA locus is independent of the major risk for RA from HLA-DRB1 SE alleles, given that no significant interaction between rs3087456 and SE alleles was observed. Since a biological link between products of these genes is evident, the genetic contribution from CIITA and class II antigens in the autoimmune process may involve additional unidentified factors.